2016
DOI: 10.1007/s12011-016-0906-x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Lithium and/or Selenium Treatment on Homeostasis of Chosen Bioelements in Rats

Abstract: Lithium is widely used in medicine and the therapy is often long term. Apart from beneficial effects, its application can cause diverse side effects. The current study was performed with the aim of the evaluation of the effect of lithium and/or selenium administration on magnesium, calcium and silicon levels in rats. The study was performed on rats divided into four groups (six animals each): control—received saline, Li—received Li2CO3 (2.7 mg Li/kg b.w.), Se—received Na2SeO3·H2O (0.5 mg Se/kg b.w.), and Li+Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Previous studies by the authors of the current study revealed the influence of treatment with lithium carbonate on calcium [13]. The presented study was extended to investigate the effect of lithium on the essential microelements.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Previous studies by the authors of the current study revealed the influence of treatment with lithium carbonate on calcium [13]. The presented study was extended to investigate the effect of lithium on the essential microelements.…”
Section: Discussionmentioning
confidence: 78%
“…Additionally: 1) selenium has already been revealed to show protective action against side effects of some drugs [11]; 2) the search for protective agents against lithium toxicity has been already performed and some antioxidants have been found to be effective [9,12]. Previous studies by the authors have shown that selenium application could change the effects of lithium on bioelements homeostasis in the organism [13]. Therefore, the research was extended to study the effect of simultaneous treatment with selenium and lithium on chosen microelements homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Selenium is incorporated into proteins via the rare amino acid selenocysteine (Sec), and this incorporation occurs during that protein translation [14,15]. Selenium and selenoproteins may participate extensively in key biological processes, such as protein folding, cellular differentiation, cellular response to oxidative stress, and the immune response.…”
Section: Discussionmentioning
confidence: 99%